OPTIMASI DAYA LASER PADA SPEKTROMETER FOTOAKUSTIK LASER CO2 KONFIGURASI INTRAKAVITAS DAN APLIKASINYA DALAM MENGUKUR KONSENTRASI GAS ASETON PADA GAS HEMBUS NAPAS PASIEN PENDERITA DIABETES MELLITUS TIPE 2 - , Ananta Kusuma Yoga Pratama ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The laser power optimization of CO2 laser photoacoustic spectrometer intracavity configuration has been conducted. It was generated 4 laser group and highest power was obtained at 53,1±0,1 W with medium active gas composition He:N2:CO2 was 48:64:80. The highest laser absorption line of standard acetone gas was determined at 9P32 and lowest detection limit was obtained at 2,2±0,04 ppb. Furthermore, photoacoustic spectrometer was used to measure gas concentration of acetone in breath sample of type 2 diabetes mellitus patient volunteers and healthy volunteers as control which each of volunteers amount 10 person. The lowest aceton concentration for patient with type 2 diabetes mellitus was 540±6 ppb and the highest concentration was 1050±8 ppb. For healthy volunteers, the highest aceton concentration was 520±6 ppb.